2011
DOI: 10.1074/jbc.m111.310920
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein K Binds Multiprotein Complexes and Is Involved in the Regulation of Endoplasmic Reticulum Homeostasis

Abstract: Background: Selenoprotein K (SelK) is an endoplasmic reticulum (ER) protein of unknown function. Results: SelK associates with proteins involved in elimination of misfolded proteins from the ER. Conclusion: SelK is a functional component of ER homeostasis.Significance: This study defines a new family of selenoproteins and links it to an ER-associated degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
131
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 53 publications
1
131
0
1
Order By: Relevance
“…95 Derlin-1 and -2 are strong candidates to play the role of channel proteins responsible for the retrotranslocation of unfolded proteins from the ER to the cytosol, the early stage of ERAD. Recent studies have shown that both SelS and SelK are associated with Derlins and p97 ATPase, with which may form an ER-membrane associate complex.…”
Section: Selenoproteins S and Kmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Derlin-1 and -2 are strong candidates to play the role of channel proteins responsible for the retrotranslocation of unfolded proteins from the ER to the cytosol, the early stage of ERAD. Recent studies have shown that both SelS and SelK are associated with Derlins and p97 ATPase, with which may form an ER-membrane associate complex.…”
Section: Selenoproteins S and Kmentioning
confidence: 99%
“…Recent studies have shown that both SelS and SelK are associated with Derlins and p97 ATPase, with which may form an ER-membrane associate complex. 95 SelS may mediate the interaction of cytosolic p97 and Derlin-1, 96 but such an assumption still needs to be confirmed. Additional partners of SelS in the complex may be required to exploit its function, and SelK seems to be a potential candidate.…”
Section: Selenoproteins S and Kmentioning
confidence: 99%
“…3, A and B) (25). Both SelS and SelK are involved in the ERAD complex and associate with p97(VCP) and derlins (12,24,25). It is well known that SelS functions in cell survival by regulating ER stress (17,26).…”
mentioning
confidence: 99%
“…SelS, which is also known as VCP-interacting membrane protein, is a selenoprotein that contains a single selenocysteine (Sec, U) at position 188, which is the penultimate C-terminal residue (21)(22)(23). SelS is an important component of the ERAD complex and is localized to the ER membrane together with SelK (24). Similarly to SelS, SelK is a selenoprotein that contains a single Sec at position 92 as the penultimate C-terminal residue, but it has no VIM or coiled-coil domain (Fig.…”
mentioning
confidence: 99%
“…Among them, selenoprotein K (SEPK) has a role in the immune system (28) , whereas selenoprotein N affects Ca homoeostasis (29) and selenoprotein P (SEPP) has an antioxidant protection function (30) . Moreover, transfer RNA (tRNA) selenocysteine 1-associated protein 1b (SECP43) has a major role in SEP synthesis by inserting selenocysteine into SEP (31) .…”
mentioning
confidence: 99%